A CCRK-EZH2 epigenetic circuitry drives hepatocarcinogenesis and associates with tumor recurrence and poor survival of patients - Feng, Hai; Yu, Zhuo; Tian, Yuan; Lee, Ying-Ying; Li, May S.; Go, Minnie Y.Y.; Cheung, Yue-Sun; Lai, Paul B.S.; Chan, Andrew M.L.; To, Ka-Fai; Chan, Henry L.Y.; Sung, Joseph J.Y.; et al. (Journal of hepatology, 2015)
[Display omitted] Aberrant chromatin modification is a key feature of hepatocellular carcinoma (HCC), which is characterized by strong sexual dimorphism. Both enhancer of zeste homolog 2 (EZH2) and cell cycle-related kinase (CCRK) contribute to hepatocarcinogenesis, yet whether the two oncogenic factors have functional crosstalk is unknown. Cellular proliferation and tumorigenicity upon transgenic expression and RNA interference were determined by colony formation and soft agar assays, xenograft, orthotopic and diethylnitrosamine-induced HCC models. Gene regulation was assessed by chromatin immunoprecipitation, site-directed mutagenesis, luciferase reporter, co-immunoprecipitation and expression analyses. Protein levels in clinical specimens were correlated with clinicopathological parameters and patient survival rates. Ectopic CCRK expression in immortalized human liver cells increased EZH2 and histone H3 lysine 27 trimethylation (H3K27me3) to stimulate proliferation and tumor formation. Conversely, knockdown of CCRK reduced EZH2/H3K27me3 levels and decreased HCC cell growth, which could be rescued by EZH2 over-expression. Mechanistically, GSK-3β phosphorylation by CCRK activated a β-catenin/TCF/E2F1/EZH2 transcriptional feedback loop to epigenetically enhance androgen receptor (AR) signaling. Simultaneously, the phosphorylation of AKT/EZH2 by CCRK facilitated the co-occupancy of CCRK promoter by EZH2-AR and its subsequent transcriptional activation, thus forming a self-reinforcing circuitry. Lentiviral-mediated knockdown of CCRK, which abrogated the phosphorylation-transcriptional network, prevented diethylnitrosamine-induced tumorigenicity. More importantly, the hyperactivation of the CCRK-EZH2 circuitry in human HCCs correlated with tumor recurrence and poor survival. These findings uncover an epigenetic vicious cycle in hepatocarcinogenesis that operates through reciprocal regulation of CCRK and EZH2, providing novel therapeutic strategy for HCC.